2016
DOI: 10.1016/j.brainres.2016.01.056
|View full text |Cite
|
Sign up to set email alerts
|

Brain stimulation: Neuromodulation as a potential treatment for motor recovery following traumatic brain injury

Abstract: There is growing evidence that electrical and magnetic brain stimulation can improve motor function and motor learning following brain damage. Rodent and primate studies have strongly demonstrated that combining cortical stimulation (CS) with skilled motor rehabilitative training enhances functional motor recovery following stroke. Brain stimulation following traumatic brain injury (TBI) is less well studied, but early pre-clinical and human pilot studies suggest that it is a promising treatment for TBI-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 104 publications
(161 reference statements)
0
22
0
Order By: Relevance
“…Stem cell implantation combined with EE and therapies directed at attenuating neuroinflammation produced the highest number of successes and thus these viable promising approaches warrant continued research. Other non-pharmacological therapies that have shown some success when provided singly include electrical and magnetic brain stimulation (Li et al, 2015; Zhang et al, 2015; Clayton et al, 2016), constrained-induced movement therapy (Brady and Garcia, 2009) and low-level laser therapy (Oron et al, 2012; Xuan et al, 2013) and may potentially be more effective when augmented by a secondary therapy. Lastly, it is important that potential therapies be evaluated by several independent groups so that the results are replicated.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell implantation combined with EE and therapies directed at attenuating neuroinflammation produced the highest number of successes and thus these viable promising approaches warrant continued research. Other non-pharmacological therapies that have shown some success when provided singly include electrical and magnetic brain stimulation (Li et al, 2015; Zhang et al, 2015; Clayton et al, 2016), constrained-induced movement therapy (Brady and Garcia, 2009) and low-level laser therapy (Oron et al, 2012; Xuan et al, 2013) and may potentially be more effective when augmented by a secondary therapy. Lastly, it is important that potential therapies be evaluated by several independent groups so that the results are replicated.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no effective therapies have yet been proven for TBI [2]. Transcranial direct current stimulation (tDCS) has emerged as a promising electroceutical therapeutic intervention suggested for TBI [3]; however, the mechanisms and optimal stimulation parameters have not yet been determined due to the lack of pre-clinical studies. Altered neuronal excitability is believed to underlie the immediate effects of tDCS; however, recent studies have shown that astrocytes are another possible target.…”
Section: Introductionmentioning
confidence: 99%
“…Of the currently registered clinical trials using rTMS or tDCS for treatment of stroke or TBI, 85% are focused on stroke recovery (as of Dec 2019- Figure 3). Research on the applicability of NIBS as an intervention for recovery of motor deficits is in the nascent stages in TBI as compared to stroke (6,189,190). Despite this rapidly increasing interest in clinical applications, there is little consensus on the efficacy of such treatment protocols [for systematic reviews and meta-analyses, see (191)(192)(193)(194)(195)(196)(197)(198)].…”
Section: Neuromodulation For Motor Recovery Post-brain Injury Neurostmentioning
confidence: 99%
“…Given that reach-to-grasp movements are a fundamental skill for many daily activities, improving reach-tograsp recovery after brain injury is a major goal of neurorehabilitation therapies (3,4). Non-invasive brain stimulation (NIBS) is of interest as both a prognostic tool for predicting motor recovery after brain injury and as a novel option for rehabilitation treatment (5)(6)(7)(8). When used as an intervention in clinical populations, NIBS techniques such as transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) have been shown to modulate localized regions of activity in the cortex and are administered either independently or in combination with task-specific training to promote functional recovery.…”
Section: Introductionmentioning
confidence: 99%